The effectiveness of a volleyball injury prevention program tailored to youth players - Nauta, J.; Gouttebarge, V.; Kemler, E.; Lang, M.; Vriend, I.; Wit, J.; Zomerdijk, D.; Zuidema, V.; Zwerver, H.; Verhagen, E. (British Journal of Sports Medicine, 2021)
Background In the Netherlands, volleyball is ranked among the top 5 sports with the highest number of injuries, and over 35% of these injuries are sustained by youth players.